A study of the effectiveness of local exhaust ventilation (LEV) in training facilities building using computational fluid dynamics (CFD) approach - Ng, Chee Seng (2013)
The purpose of this study is to identify effectiveness of local exhaust ventilation (LEV) systems and to validate computational fluid dynamics (CFD) simulation results with actual experimental results. Three case studies had been conducted at Ventilation Laboratory in National Institute of Occupational Safety and Health (NIOSH) Bangi, Welding Laboratory and Thermal Environmental Laboratory in Universiti Tun Hussein Onn Malaysia (UTHM). LEV is a ventilation system that captures contaminants, for example dusts, mists, gases, vapours or fumes out from workstations, so that they can‟t be breathed by occupants. Employers allocate and install LEV in order to protect occupants‟ exposure to contaminants, but it doesn‟t work properly. To overcome this issue, Guidelines on Occupational Safety and Health for Design, Inspection, Testing and Examination of LEV system and CFD can be implemented. The guideline stated that the recommended minimum hood velocity is 100 ft/min; while the recommended velocity along ducts for vapours, gases, smoke is 1000 ft/min and 2000 ft/min is required for welding. It was found that Ventilation Laboratory in NIOSH Bangi using Control Speed of 80%, Welding Laboratory and Thermal Environmental Laboratory in UTHM met all the minimum requirements set by the guideline, where LEV systems are effective to be used. In terms of CFD modeling, upon validation, average absolute error obtained from three case studies ranges from 2.804% and 4.862%. Validity of CFD modeling is acceptable, which is less than 5% and good agreement is achieved between actual experimental results and CFD simulation results. Therefore, it can be concluded that simple CFD modeling can be performed as a tool to simulate air velocity in LEV system, which saves labour costs and time consumption when it is used during earliest stage of LEV design development prior to actual construction. The outcome of this study can be used as a benchmark or guideline for training facilities building equipped with LEV system to protect occupants‟ health.